2010
DOI: 10.1128/jvi.02256-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus TR Strain Glycoprotein O Acts as a Chaperone Promoting gH/gL Incorporation into Virions but Is Not Present in Virions

Abstract: Human cytomegalovirus (HCMV) produces the following two gH/gL complexes: gH/gL/gO and gH/gL/ UL128-131. Entry into epithelial and endothelial cells requires gH/gL/UL128-131, and we have provided evidence that gH/gL/UL128-131 binds saturable epithelial cell receptors to mediate entry. HCMV does not require gH/gL/UL128-131 to enter fibroblasts, and laboratory adaptation to fibroblasts results in mutations in the UL128-131 genes, abolishing infection of epithelial and endothelial cells. HCMV gO-null mutants produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
60
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 56 publications
8
60
1
Order By: Relevance
“…The loss of UL128-131 appears to be an adaptation to growth in fibroblasts, because viruses without UL128-131 apparently possess a selective advantage when growing in these cells. HCMV also expresses another glycoprotein, gO, that forms distinct complexes with gH/gL that are necessary for HCMV entry into human fibroblasts (14,15,17,19,27,38,40). These observations fit with the notion that all herpesviruses rely on gH/gL complexes for entry into cells (31).…”
supporting
confidence: 75%
See 4 more Smart Citations
“…The loss of UL128-131 appears to be an adaptation to growth in fibroblasts, because viruses without UL128-131 apparently possess a selective advantage when growing in these cells. HCMV also expresses another glycoprotein, gO, that forms distinct complexes with gH/gL that are necessary for HCMV entry into human fibroblasts (14,15,17,19,27,38,40). These observations fit with the notion that all herpesviruses rely on gH/gL complexes for entry into cells (31).…”
supporting
confidence: 75%
“…We had previously shown that with HFFs and MRC-5 cells, it was necessary to use higher doses of Ad vectors expressing gH, gL, UL128, UL130, and UL131 (90 PFU/cell of each vector) in order to match the levels of gH/gL expression to those in ARPE-19 cells (10 PFU/cell) (26). The Ad vector that expresses TRgO(co) was codon optimized and expresses very high levels of gO and was used at 3 PFU/cell based on previous analyses of expression, again matching gO expression to that of gH/gL and UL128-131 (27). Following 24 h of transduction with Ad vectors, cells were infected with HCMV TR (2 PFU/cell) for an additional 48 h, and the cells were then stained for the immediate-early protein IE-86 as described previously (26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations